The Predictive Effects of Self-Esteem, Moral Self, and Moral Reasoning on Delinquent Behaviors of Hong Kong Young People - Cheng, Christopher (International Journal of Criminology and Sociology, 2014)
While external factors such as family and peers were widely known to be predictive of juvenile delinquency, mixed results were reported regarding the effects of internal (personal) variables such as self-concept and moral reasoning maturity. The present study was to delineate the effects of two variables relating to the self (self-esteem, moral self) and the moral reasoning maturity in predicting delinquency. A sample of 266 young people aged between 17 and 21 were invited to complete a questionnaire composed of global self-concept (self-esteem) scale, moral self scale, moral reasoning test, and a daily behavior checklist. Regression and correlation analyses indicated that moral self and moral reasoning were in general negatively associated with delinquency, but global self-esteem did not have significant linear relation with delinquency. Polynomial contrast tests revealed that moral reasoning and moral self to certain extent had a linear trend with delinquency negatively, but global self-esteem exhibited a curvilinear (U-shape) trend with some but not all delinquent behaviors such as sexual misconduct, drug offenses, gambling. The results were then discussed in the light of self-derogation theory and other relevant theories such as the "threatened ego" and the multidimensional model of self-concept, and hopefully could throw lights to explain the phenomenon for further research.